An integrated approach for fuzzy failure modes and effects analysis using fuzzy AHP and fuzzy MAIRCA - Boral, Soumava; Howard, Ian; Chaturvedi, S.K.; McKee, Kristoffer; Naikan, V.N.A. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
© 2019 Elsevier Ltd